RapGreen, an interactive software and web package to explore and analyze phylogenetic trees. (23rd September 2021) - Dufayard, Jean-François; Bocs, Stéphanie; Guignon, Valentin; Larivière, Delphine; Louis, Alexandra; Oubda, Nicolas; Rouard, Mathieu; Ruiz, Manuel; de Lamotte, Frédéric
Abstract: RapGreen is a modular software package targeted at scientists handling large datasets for phylogenetic analysis. Its primary function is the graphical visualization and exploration of large trees. In addition, RapGreen offers a tree pattern search function to seek evolutionary scenarios among large collections of phylogenetic trees. Other functionalities include tree reconciliation with a given species tree: the detection of duplication or loss events during evolution and tree rooting. Last but not least, RapGreen features the ability to integrate heterogeneous data while visualizing and otherwise analyzing phylogenetic trees.